Modeling communication system components for prediction of RF performance - Lim, Seok Tien. (2009)
A process to model components specifications in RF front-end system is being demonstrated through a series of exploring basic fundamental of components and software simulators. The main objective of this report is to investigative the individual component specification in RF front-end system. Low Noise Block from Agilis Communications Technologies Pte Lte were use to perform the investigation in this report. Components’ parameters used in the system are described in detail and derivation of component specification is included. In addition effects of cascading the component in the system were also discussed. Various types of simulator tools in ADS are being introduced and the basic setting requirement is covered in the report. Lastly the method of modeling of component parameter and result are obtain and discussed.